2016
DOI: 10.1007/s00464-016-4990-y
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss and improvement of lipid profiles in morbidly obese patients after laparoscopic one-anastomosis gastric bypass: 2-year follow-up

Abstract: OAGB leads to substantial and durable WL in morbidly obese patients after a 2-year follow-up. Postoperative lipid profiles significantly improved; these changes translate into theoretical relevant cardiovascular risk benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 24 publications
2
16
0
1
Order By: Relevance
“…Once WL was being achieved, other “mechanical”-related comorbidities were also abated. We recently published results from selected patients included in the IFSO-European Accreditation Council (EAC) for Centers of Excellence database with insulin resistance/type 2 DM [32] or lipid profile derangements [36]. Substantial WL and significant improvement or full remission from their metabolic condition was observed in both series.…”
Section: Discussionmentioning
confidence: 99%
“…Once WL was being achieved, other “mechanical”-related comorbidities were also abated. We recently published results from selected patients included in the IFSO-European Accreditation Council (EAC) for Centers of Excellence database with insulin resistance/type 2 DM [32] or lipid profile derangements [36]. Substantial WL and significant improvement or full remission from their metabolic condition was observed in both series.…”
Section: Discussionmentioning
confidence: 99%
“…In regard to the safety profile of laparoscopic OAGB, according to the currently available evidence, there are acceptable early and late complication rates, and the frequency of symptomatic bile reflux is lower than firstly feared, although this information mainly relies on self-reporting (7,(24)(25)(26) .…”
Section: Discussionmentioning
confidence: 99%
“…All these mechanisms are conducted to avoid bile reflux. However, gastric physiology is not only a mechanical event 4 , 33 , 37 , 6 , 30 , 55 , 48 , 32 , 42 , 8 , 7 . Up to now in the available literature concerning to SAGB, only clinical studies have been reported, specially focused in the weight loss and improvement of comorbidities.…”
Section: Discussionmentioning
confidence: 99%